Profile of everolimus in the treatment of tuberous sclerosis complex: an evidence-based review of its place in therapy - Capal J; Franz DN (Neuropsychiatric Disease and Treatment)
Jamie K Capal, David Neal Franz Department of Neurology, Cincinnati Children’s Hospital Medical Center, Cincinnati, OH, USA Abstract: Tuberous sclerosis complex (TSC) is a relatively rare genetic disorder, affecting one in 6,000 births. Mammalian target of rapamycin (mTOR) inhibitors, such as everolimus, which have been previously used to prevent solid organ transplant rejection, augment anticancer treatment regimens, and prevent neovascularization of artificial cardiac stents, are now approved for treating TSC-related manifestations, such as subependymal giant cell astrocytomas and renal angiomyolipomas. The use of everolimus in treating subependymal giant cell astrocytomas is supported by long-term Phase II and III clinical trials. Seizures are a common feature in TSC, occurring in up to 96% of patients. While mTOR inhibitors currently do not have regulatory approval in treating this manifestation, small clinical studies have demonstrated beneficial outcomes with everolimus. Further evidence from a forthcoming Phase III clinical study may provide additional support for the use of everolimus for this indication. Also, there are no approved treatments for TSC-associated neuropsychiatric disorders, which include intellectual disability, behavioral difficulties, and autism spectrum disorder, but preclinical data and small studies have suggested that some neuropsychiatric symptoms may be improved through mTOR inhibition therapy. More evidence is needed, particularly regarding safety in young infants. This review focuses on the current evidence supporting the use of everolimus in neurologic and neuropsychiatric manifestations of TSC, and the place of everolimus in therapy. Keywords: everolimus, tuberous sclerosis complex, subependymal giant cell astrocytomas, seizures, TAND